ORAL DISCOURSE GENERATED THROUGH PEER-INTERACTION WHILE COMPLETING COMMUNICATIVE TASKS IN AN EFL CLASSROOM - Golda J. Tulung (TEFLIN Journal: A publication on the teaching and learning of English, 2013)
Drawing on qualitative observation data from a case study of an EFL classroom for pre-medical students in an Indonesian university, this article examines the oral discourse generated through peer interaction while completing two types of communicative tasks in terms of how much language was generated, includingthe amount of the L2 generated and the useof the L1. Findings indicate that the use of communicative tasks in this specific EFL context appears to provide students with opportunities for L2 production and to diminish L1 use in class. This is largely determined by the communicative tasks used and the EFL context.Â